Risk Factors of urinary tract infection in preschool children in Dhaka, Bangladesh - Ferdaus, Jannatul; Moinuddin, Golam; Islam, Mohammad Tariqul; Rashid, Md Harun Or; Shawly, Mahjabin Rahman; Alim, Abdul (Bangladesh Medical Journal, 2017)
Urinary Tract Infection (UTI) is the leading cause of death in children below five years of age in Bangladesh. Identification of modifiable risk factors of UTI may reduce the chances of the disease. This hospital based case-control study was conducted from January 2008 to December 2008 in Bangabandhu Sheikh Mujib Medical University, Dhaka to determine risk factors associated with UTI in preschool children. A group of 201 children with UTI on the basis of urgency and frequency in micturition & lower abdominal pain with or without fever were considered as case subjects under this study. Analysis was conducted comparing data from case group against a control group of 311 healthy children who were reported to have no fever and abdominal pain. Wiping (from back to front), circumcision status, nappy use, obstructive uropathy, neurogenic bladder, poor personal hygiene and constipation were found to be potential factors for UTI under logistic regression. Among them, nappy use was the main contributing factor and circumcision status and constipation were the second and third largest contributing factors for UTI. Age and sex had no statistically significant association. Bangladesh Med J. 2016 Sep; 45 (3): 134-137